Staple security : bread and wheat in Egypt - Barnes, Jessica, 1978- (Duke University Press, 2022)
"Egyptians often say that bread is life; most eat this staple multiple times a day, many relying on the cheap bread subsidized by the government. In Staple Security, Jessica Barnes explores the process of sourcing domestic and foreign wheat for the production of bread and its consumption across urban and rural settings. She traces the anxiety that pervades Egyptian society surrounding the possibility that the nation could run out of wheat or that people might not have enough good bread to eat, and the daily efforts to ensure that this does not happen. With rich ethnographic detail, she takes us into the worlds of cultivating wheat, trading grain, and baking, buying, and eating bread. Linking global flows of grain and a national bread subsidy program with everyday household practices, Barnes theorizes the nexus between food and security, drawing attention to staples and the lengths to which people go to secure their consistent availability and quality."--